The Effectiveness of the Water Additional Ingredient Urea CO(NH2)2 to the Concrete Fc' 20 MPA on Curing Process - Hafiq Syaifudin; Rio Rahma Dhana (Litbang Pemas - Universitas Islam Lamongan, 2022)
Concrete quality depends on the value of the ratio of materials, how to blend and how to pour the concrete mixture, how to compact and how to care for it during the hardening process. This study aims to determine how much influence the curing process using water with a mixture of Co(NH2)2 and normal water has on the compressive strength of concrete fc' 20 Mpa. The sample is a cylindrical specimen with a diameter of 15 cm and a height of 30 cm. Samples were made 3 test objects with the age of 28 days and tested coherently. The compressive strength of normal concrete has increased in quality with the age between 7 is 9.1 Mpa to 28 days is 17 Mpa. While the concrete with curring process using water with a mixture of urea increased at age 7 with a value of 10.8 Mpa to 21 days with a value of 14.4 Mpa, but at age 28 the strength of the concrete decreased by 12 Mpa. Cracks with cone and split types are 10 pieces, this can happen because the material in the concrete mixer has not been mixed well during the concrete manufacturing process.